(untitled) (Texas Journal of Engineering and Technology, 2023)
In this article, measures to further improve the existing transport service organization system in our Republic, complex motor transport enterprises that include technical service and repair of cars, storage, fuel-lubrication and provision of spare parts. activities such as the plan of increasing the number of vehicles, the implementation of technological equipment, reconstruction and improvement of existing motor transport enterprises based on the requirements of the times were analyzed.